Responses of Nitrogen-Cycling Microorganisms to Dazomet Fumigation - Fang, Wensheng; Yan, Dongdong; Wang, Xianli; Huang, Bin; Wang, Xiaoning; Liu, Jie; Liu, Xiaoman; Li, Yuan; Ouyang, Canbin; Wang, Qiuxia; Cao, Aocheng (Frontiers in Microbiology, 2018)
The influence of soil fumigation on microorganisms involved in transforming nitrogen remains little understood, despite the use of fumigants for many decades to control soil-borne pathogens and plant-parasitic nematodes. We used real-time PCR (quantitative polymerase chain reaction) and 16S rRNA gene amplicon sequencing techniques to monitor changes in the diversity and community structure of microorganisms associated with nitrogen transfer after the soil was fumigated with dazomet (DZ). We also examined N2O emissions from these microorganisms present in fumigated fluvo-aquic soil and lateritic red soil. Fumigation with DZ significantly reduced the abundance of 16S rRNA and nitrogen cycling functional genes (nifH, AOAamoA, AOB amoA, nxrB, narG, napA, nirK, nirS, cnorB, qnorB and nosZ). At the same time, N2O production rates increased between 9.9 to 30 times after fumigation. N2O emissions were significantly correlated with NH4+, dissolved amino acids and microbial biomass nitrogen, but uncorrelated with functional gene abundance. Diversity indices showed that DZ temporarily stimulated bacterial diversity as well as caused a significant change in bacterial community composition. For example, DZ significantly decreased populations of N2-fixing bacteria Mesorhizobium and Paenibacillus, nitrifiers Nitrosomonas, and the denitrifiers Bacillus, Pseudomonas and Paracoccus. The soil microbial community had the ability to recover to similar population levels recorded in unfumigated soils when the inhibitory effects of DZ fumigation were no longer evident. The microbial recovery rate, however, depended on the physicochemical properties of the soil. These results provided useful information for environmental safety assessments of DZ in China, for improving our understanding of the N-cycling pathways in fumigated soils, and for determining the potential responses of different N-cycling groups after fumigation.